Relationship between age, education and blood zinc levels, with cognitive function in menopausal women - Pandhita, Gea; Mawi, Martiem; Nuryani, Mieke (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: The increase in life expectancy results in an increase in the number of elderly, especially menopausal women. Aging can have an impact on the decline of cognitive function. The decline in cognitive function and being influenced by age can also be affected by education and blood zinc levels. However, various research results still need to be more conclusive regarding how much influence age, education, and blood zinc levels have on cognitive function. Objectives: To determine the relationship between age, education, and blood zinc levels with the cognitive function of elderly menopausal women. Methods: This research is analytical research with a cross-sectional design. The subjects of the study were menopausal women aged 60 years and over who was able to walk without help, as well as being able to read and write. Study subjects who suffered from a stroke, heart, kidney, mental function disorders, and used drugs for mental disorders, were not included in this study. Research subjects who met the eligibility criteria were carried out with physical examinations (age, height, weight, blood pressure) and laboratory examinations (blood sugar ad random and blood zinc levels), as well as undergoing cognitive function tests using MoCA-INA. Results: A total of 65 study subjects met the eligibility criteria. Multivariate statistical analysis showed that there was a correlation between the cognitive function of the attention domain with age (r=0.278, p=0.030), the cognitive function of the visuospatial domain with education (r=0.528, p=<0.001), the cognitive function of the language domain with blood zinc levels (r=-0.279, p=0.019) and the cognitive function of the orientation domain with education (r=0.319, p=0.012). Conclusions: The results of this study show that there is a meaningful relationship between age, education, and blood zinc levels, with cognitive function in elderly menopausal women.